2016
DOI: 10.1093/cercor/bhv310
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-Dependent Calcium Oscillations of Astrocytes: An Implication for Pathology

Abstract: Astrocytes in various brain regions exhibit spontaneous intracellular calcium elevations both in vitro and in vivo; however, neither the temporal pattern underlying this activity nor its function has been fully evaluated. Here, we utilized a long-term optical imaging technique to analyze the calcium activity of more than 4000 astrocytes in acute hippocampal slices as well as in the neocortex and hippocampus of head-restrained mice. Although astrocytic calcium activity was largely sparse and irregular, we obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 91 publications
0
12
0
1
Order By: Relevance
“…Ca 2+ dynamics, including amplitude, duration, and frequency, may encode information of astrocytes. For example, in situ imaging data indicate that Ca 2+ oscillations are associated with hypertrophy of astrocytes [49]. Therefore, exploring Ca 2+ signals in reactive astrocytes provides insight into functional changes.…”
Section: Ca2+ Signals In Reactive Astrocytesmentioning
confidence: 99%
“…Ca 2+ dynamics, including amplitude, duration, and frequency, may encode information of astrocytes. For example, in situ imaging data indicate that Ca 2+ oscillations are associated with hypertrophy of astrocytes [49]. Therefore, exploring Ca 2+ signals in reactive astrocytes provides insight into functional changes.…”
Section: Ca2+ Signals In Reactive Astrocytesmentioning
confidence: 99%
“…Astrocyte-induced glutamate-mediated SICs of thalamo-cortical neurons seem to be dependent on extracellular glutamate levels, since exogenous exposure to the glutamate-mimetic D-aspartate increased the frequency of SICs ( 243 ). Although it is still unclear if abnormal or hypersynchronous astroglial Ca 2+ signals could promote epileptiform network activity by itself, this evidence further supports an astroglial contribution to the propagation and self-sustain of seizure-like activity ( 244 , 245 ).…”
Section: Astrocytes Contribute To Network Priming and Synchronization As Well As Swd Induction Propagation And Terminationmentioning
confidence: 53%
“…Oscillatory gating dynamics of plasma-membrane-embedded channels or cyclic calcium release from intracellular stores can generate calcium spikes ( 23 ). Changes in the amplitude and frequency of these oscillating signals along with the intracellular concentrations of these second messengers can trigger diverse cellular responses in neurons ( 23 , 52 , 53 , 54 ). Studies have shown that calcium oscillates spontaneously in spines ( 55 ) and that CaMKII activity is sensitive to calcium frequency ( 56 , 57 , 58 , 59 , 60 ).…”
Section: Introductionmentioning
confidence: 99%